2018
DOI: 10.1107/s2052520618002962
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, phase transition and structural deformations in iron borate (Y0.95Bi0.05)Fe3(BO3)4in the temperature range 90–500 K

Abstract: An accurate X-ray diffraction study of (YBi)Fe(BO) single crystals in the temperature range 90-500 K was performed on a laboratory diffractometer and used synchrotron radiation. It was established that the crystal undergoes a diffuse structural phase transition in the temperature range 350-380 K. The complexity of localization of such a transition over temperature was overcome by means of special analysis of systematic extinction reflections by symmetry. The transition temperature can be considered to be T ≃ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…However, it is lower than T str = 174 K, found by Hinatsu et al (2002). An analysis of systematic extinction determined that a diffuse phase transition in (Y 0.95 Bi 0.05 )-Fe 3 (BO 3 ) 4 occurs at about 370 K (Frolov et al, 2018;Smirnova et al, 2018). This is close to T str = 350 K found by Fausti et al (2006), but lower than T str = 445 K for powder samples (Hinatsu et al, 2002).…”
Section: Introductionmentioning
confidence: 45%
See 4 more Smart Citations
“…However, it is lower than T str = 174 K, found by Hinatsu et al (2002). An analysis of systematic extinction determined that a diffuse phase transition in (Y 0.95 Bi 0.05 )-Fe 3 (BO 3 ) 4 occurs at about 370 K (Frolov et al, 2018;Smirnova et al, 2018). This is close to T str = 350 K found by Fausti et al (2006), but lower than T str = 445 K for powder samples (Hinatsu et al, 2002).…”
Section: Introductionmentioning
confidence: 45%
“…To study the structure of the single crystal above and below the phase transition temperature T str , we obtained complete sets of X-ray diffraction data at 90,293,350,360,365,370,380,390 and 500 K using the Rigaku Oxford CCD Xcalibur EOS S2 X-ray diffractometer, equipped with a Cobra Plus (Oxford Cryosystems) temperature device with a laminar flow of nitrogen gas. The temperature of the transition T str was assumed to be 360 K (Erofeev et al, 2016), 427 K (Hinatsu et al, 2002) or close to the temperature of 370 K found for (Y 0.95 Bi 0.05 )Fe 3 (BO 3 ) 4 (Smirnova et al, 2018).…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations